Legal Protection of Foreign Investment in South Africa - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
Foreign Direct Investment (FDI) is regarded as a key contributor to economic growth and wealth creation in both developing and developed countries. It is for this reasons that countries compete on the international stage to attract the limited amount of FDI that is available internationally. Countries compete for this limited amount of investment by a number of means but one of the most important factors is the protection of investments. Countries offer foreign investors certain protections to guarantee that they may safely and securely invest in that specific country. By establishing these protections countries hope that foreign investors will choose that country to invest in. The main instruments that have been used in recent years to offer this protection are treaties. These treaties are commonly known as bilateral investment treaties or BITs. South Africa is no exception and the country has concluded BITs with a number of other nations to offer investors this protection. The main purpose of such BITs are to ensure the protection of investments and also to promote foreign investment. These BITs do however place significant obligations on its parties and they may not always be beneficial. As a result of the risks related to these treaties the South African government decided to terminate many of its BITs. The cancellation of these BITs has however left a gap with regards to investment protection in South Africa. The South African government accordingly decided to fill this gap by way of domestic legislation. This legislation is the so-called Protection of Investment Act. It intends to protect investments in South Africa while at the same time achieving a balance between investor protection and public interest. The history of South Africa's investment regime is largely similar to what was seen internationally at any given time. In recent years however the cancelation of BITs and the Protection of Investment Act has been a departure from the international norm. A comparison of the Protection of Investment Act and some South African BITs reveal that there are some major differences between the two types of instruments. The Act clearly offers less robust protections when compared to South African BITs. A closer analysis of the provisions of the Act also reveals that the Act in itself significantly departs from international standards relating to investor protection. It further appears that the Act over-emphasises public interest at the expense of investor protection. The cancellation of many BITs together with the enactment of the Protection of Investment Act has significantly altered South Africa's investment regime. Taking into account South African BITs and international standards it is clear that investor protection has been greatly weakened in the country. On the other hand, government now has far greater flexibility when it comes to regulation that may affect a foreign investor. This reduction in protection may however unfortunately lead to a decrease in investor confidence in South Africa.